High-adhesion underfill adhesive, preparation method thereof and chip packaging structure
By combining the crosslinking reaction of epoxy resin and acid anhydride curing agent with liquid bismaleimide, the problems of insufficient wettability and adhesion between the bottom filler and the PI substrate were solved, achieving rapid curing and efficient encapsulation.
Patent Information
- Application Number
- CN202511374645.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2025-12-02
AI Technical Summary
The underfill adhesive in the existing technology has poor wettability between the PI substrate and the chip during the COF packaging process, which easily forms voids and bubbles, and has low adhesion, affecting chip packaging efficiency.
The curing reaction is achieved by crosslinking epoxy resin with an anhydride curing agent to generate polar groups that form hydrogen bonds and van der Waals forces. Liquid bismaleimide is used to reduce the surface energy difference, improve wettability and adhesion, and an imidazole accelerator is used to accelerate the curing reaction.
This technology enables the underfill adhesive to be completely wetted and cured in a short time, avoiding bubbles and voids, improving adhesion to the PI substrate, and enhancing chip packaging efficiency and yield.
Smart Images

Figure CN121046009A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chip packaging technology, and specifically relates to a strong adhesive bottom filler, its preparation method, and a chip packaging structure. Background Technology
[0002] As chip technology advances towards higher integration, smaller size, higher performance, and more demanding application environments, the technical requirements for underfill adhesives, as key packaging materials, are continuously upgrading. In COF (chip-on-film) packaging, the chip needs to be directly fixed onto a flexible PI substrate, and the underfill adhesive used for chip packaging must have strong adhesion to the flexible PI substrate. However, existing underfill adhesives have poor wetting properties between the adhesive and the PI substrate and chip, easily forming voids and bubbles. Furthermore, during pre-curing in a tunnel oven after dispensing, the adhesive's surface drying speed is slow, or the adhesion to the PI substrate or chip after curing is low, causing underfill adhesive to drip and damage equipment or deform, thus affecting chip packaging efficiency.
[0003] Therefore, how to provide a high-adhesion underfill adhesive by introducing bismaleimide into the epoxy system to improve its adhesion to the PI substrate, while shortening the surface drying time and improving chip packaging efficiency, is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0004] The purpose of this invention is to provide a high-adhesion underfill adhesive and its preparation method, as well as a chip packaging structure, so as to solve at least one of the above-mentioned technical problems.
[0005] To achieve the above objectives, the first aspect of the present invention provides a high-adhesion underfill adhesive, wherein the underfill adhesive is composed of the following components by weight percentage: 28% to 54% epoxy resin, 38% to 67% acid anhydride curing agent, 2% to 5% accelerator, and 1% to 4% additive; wherein the epoxy resin is a compound of bisphenol F type epoxy resin and alicyclic epoxy resin, and the additive includes liquid bismaleimide.
[0006] In the first aspect, the bisphenol F type epoxy resin has a mass percentage of 14% to 27%, and the alicyclic epoxy resin has a mass percentage of 14% to 27%.
[0007] In the first aspect, the bisphenol F type epoxy resin has a mass percentage of 27%, and the alicyclic epoxy resin has a mass percentage of 27%.
[0008] In the first aspect, the hydrolytic chlorine content of the epoxy resin is less than 70 ppm.
[0009] In the first aspect, the alicyclic epoxy resin has the following structural formula:
[0010]
[0011] In the first aspect, the anhydride curing agent includes methylhexahydrophthalic anhydride.
[0012] In the first aspect, the accelerator includes an imidazole-type accelerator.
[0013] The second aspect of this invention provides a method for preparing a high-adhesion underfill adhesive, the method comprising: weighing each component of the raw materials according to the mass percentage of the high-adhesion underfill adhesive described in the first aspect, and placing them in a mixing cup to obtain a first slurry; stirring the first slurry using a first centrifugal mixer to obtain a uniformly mixed second slurry; the operating parameters of the first centrifugal mixer include: stirring time of 150-240 s, rotation of 30 r / min, and revolution of 1500 r / min; and vacuum degassing the second slurry using a second centrifugal mixer to obtain the underfill adhesive; the operating parameters of the second centrifugal mixer include: stirring time of 100-200 s, rotation of 10 r / min, and revolution of 1000 r / min.
[0014] A third aspect of the present invention provides a chip packaging structure, the chip packaging structure comprising: a flexible PI substrate, a chip, and the high-adhesion underfill adhesive described in the first aspect; the underfill adhesive is filled between the flexible PI substrate and the chip.
[0015] In the third aspect, the gap height between the flexible PI substrate and the chip is 3-9 μm.
[0016] Beneficial effects:
[0017] This invention provides a high-adhesion underfill adhesive, composed of the following components by weight percentage: 28%–54% epoxy resin, 38%–67% acid anhydride curing agent, 2%–5% accelerator, and 1%–4% additives; wherein the epoxy resin is a compound of bisphenol F type epoxy resin and alicyclic epoxy resin, and the additives include liquid bismaleimide; using bisphenol F type epoxy resin and alicyclic epoxy resin as the base resin, the acid anhydride curing agent and the base resin undergo a rapid cross-linking and curing reaction at high temperature, shortening the surface drying time. Simultaneously, the polar groups generated in the reaction (such as carboxyl and hydroxyl groups) form hydrogen bonds and van der Waals forces with the polar groups (imide groups, amino groups, etc.) on the surface of the PI substrate, thereby improving the adhesion of the underfill adhesive; furthermore, liquid bismaleimide is added to the system, utilizing the similar groups of bismaleimide and PI to reduce the surface energy difference between the underfill adhesive and the PI substrate, thereby improving the wettability and adhesion of the underfill adhesive. This invention accelerates the cross-linking and curing reaction of the underfill adhesive by using an anhydride curing agent, shortening the surface drying time and making it suitable for tunnel ovens, thereby improving chip packaging efficiency. At the same time, bismaleimide is introduced into the system to reduce the surface energy difference with the PI substrate, thereby improving the adhesion between the underfill adhesive and the PI substrate and the chip, and improving the chip packaging yield. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of this specification or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 A schematic diagram of a chip packaging structure provided by the present invention;
[0020] Figure label:
[0021] 1. Flexible PI substrate; 2. Chip; 3. Underfill adhesive. Detailed Implementation
[0022] The present invention will be described in detail below with reference to specific embodiments and examples, thereby making the advantages and various effects of the present invention more clearly apparent. Those skilled in the art should understand that these specific embodiments and examples are for illustrative purposes only and are not intended to limit the present invention.
[0023] Throughout this specification, unless otherwise specified, the terminology used herein should be understood as having the meaning commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In the event of any conflict, this specification shall prevail.
[0024] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be obtained by purchasing them from the market or by existing methods.
[0025] This application provides a high-adhesion underfill adhesive, which is composed of the following components by weight percentage: 28% to 54% epoxy resin, 38% to 67% acid anhydride curing agent, 2% to 5% accelerator, and 1% to 4% additive; wherein the epoxy resin is a compound of bisphenol F type epoxy resin and alicyclic epoxy resin, and the additive includes liquid bismaleimide.
[0026] Specifically, the present invention provides a high-adhesion underfill adhesive, which is composed of the following components by mass percentage: 28%–54% epoxy resin, 38%–67% acid anhydride curing agent, 2%–5% accelerator, and 1%–4% additives; wherein the epoxy resin is a compound of bisphenol F type epoxy resin and alicyclic epoxy resin, and the additives include liquid bismaleimide; using bisphenol F type epoxy resin and alicyclic epoxy resin as the base resin, the acid anhydride curing agent and the base resin undergo a rapid cross-linking and curing reaction at high temperature, shortening the surface drying time. At the same time, the polar groups (such as carboxyl and hydroxyl groups) generated by the reaction form hydrogen bonds and van der Waals forces with the polar groups (imide groups, amino groups, etc.) on the surface of the PI substrate, thereby improving the adhesion of the underfill adhesive; furthermore, liquid bismaleimide is added to the system, utilizing the similar groups of bismaleimide and PI to reduce the surface energy difference between the underfill adhesive and the PI substrate, thereby improving the wettability and adhesion of the underfill adhesive. This invention accelerates the cross-linking and curing reaction of the underfill adhesive by using an anhydride curing agent, shortening the surface drying time and making it suitable for tunnel ovens, thereby improving chip packaging efficiency. At the same time, bismaleimide is introduced into the system to reduce the surface energy difference with the PI substrate, thereby improving the filling performance between the underfill adhesive and the PI substrate, thus improving adhesion and increasing chip packaging yield.
[0027] It should be noted that, in order to improve production efficiency, a tunnel-type oven is usually used to pre-cure the roll-to-roll flexible PI substrate after dispensing. It is required to quickly gel or surface dry within 130℃ / 3min (the heat curing conditions of the first oven section). After surface drying, when the flexible PI substrate rises to the second oven section through the hollow fixed pulley, the adhesive and the PI substrate have a certain adhesion to avoid the adhesive dripping and damaging the equipment, and to avoid deformation or extrusion cracks of the bottom filler during the winding process.
[0028] The viscosity of the additive liquid bismaleimide at 25°C is 1000-2000 cp; the structural formula of the liquid bismaleimide is shown below:
[0029]
[0030] Because bismaleimide and PI share the same group RC(O)-N(R)-C(O)-R, their surface energies are very similar and their contact angles are small. This results in good wettability of the PI substrate in the prepared underfill adhesive, allowing for complete wetting of both the PI substrate and the chip, thus preventing the formation of bubbles and voids and ensuring complete filling of gaps. Furthermore, the shared group leads to stronger intermolecular forces between them, thereby improving the adhesion between the underfill adhesive and the PI substrate.
[0031] In some possible embodiments, the bisphenol F type epoxy resin has a mass percentage of 14% to 27%, and the alicyclic epoxy resin has a mass percentage of 14% to 27%.
[0032] In some possible embodiments, the bisphenol F type epoxy resin has a mass percentage of 27%, and the alicyclic epoxy resin has a mass percentage of 27%.
[0033] In some possible embodiments, the hydrolytic chlorine content of the epoxy resin is less than 70 ppm.
[0034] In some possible embodiments, the alicyclic epoxy resin has the following structural formula:
[0035]
[0036] In this application, a low-hydrolyzable chlorine and low-viscosity epoxy resin is used, which makes the prepared adhesive liquid have good fluidity and can meet the encapsulation requirements of 3μm ultra-narrow gap; at the same time, by adjusting the ratio between bisphenol F type epoxy resin and alicyclic epoxy resin, the cross-linking and curing reaction rate of the bottom filler adhesive can be adjusted, so that it can be adapted to continuous production of the instrument.
[0037] In some possible embodiments, the anhydride curing agent includes methylhexahydrophthalic anhydride.
[0038] In some possible embodiments, the accelerator includes an imidazole-type accelerator.
[0039] In this application, an anhydride-based curing agent is selected to participate in the crosslinking and curing reaction. This utilizes the polar functional groups such as hydroxyl and carboxyl groups generated during the reaction between the epoxy resin and the anhydride-based curing agent to enhance the adhesion between the epoxy resin and the PI substrate. Simultaneously, the addition of an imidazole-type accelerator further accelerates the crosslinking and curing reaction, allowing the adhesive to quickly surface dry in the first oven section, preventing adhesive dripping and equipment damage due to insufficient adhesion during the winding process.
[0040] Based on a general inventive concept, this application also provides a method for preparing a high-adhesion underfill adhesive, the method comprising: weighing each component of the raw materials according to the mass percentage of the high-adhesion underfill adhesive described in the first aspect, and placing them in a mixing cup to obtain a first slurry; stirring the first slurry using a first centrifugal mixer to obtain a uniformly mixed second slurry; the operating parameters of the first centrifugal mixer include: stirring time of 150-240 s, rotation of 30 r / min, and revolution of 1500 r / min; and vacuum degassing the second slurry using a second centrifugal mixer to obtain the underfill adhesive; the operating parameters of the second centrifugal mixer include: stirring time of 100-200 s, rotation of 10 r / min, and revolution of 1000 r / min.
[0041] Specifically, this application provides a method for preparing a high-adhesion underfill adhesive. First, the raw material components are weighed according to a specific formula ratio and mixed evenly. Then, vacuum degassing is performed to remove air bubbles generated during the mixing process, thereby obtaining an underfill adhesive with low viscosity and good flowability at room temperature. This adhesive is then used to fill the gap between the filler chip and the PI substrate. It can be initially cured within 3 minutes at 130°C and has a certain adhesion to the PI substrate, making it suitable for the winding process and achieving rapid surface drying of the adhesive.
[0042] Based on a general inventive concept, this application also provides a chip packaging structure, which includes: a flexible PI substrate 1, a chip 2, and a high-adhesion underfill adhesive 3 as described in the first aspect; the underfill adhesive 3 is filled between the flexible PI substrate 1 and the chip 2.
[0043] In conjunction with the third aspect of this application, the gap height between the flexible PI substrate 1 and the chip 2 is 3-9 μm.
[0044] Specifically, the high-adhesion underfill provided in this application is applied to the COF chip packaging process. The underfill adhesive is applied to the edge of the gap between the flexible PI substrate 1 and the chip 2 using a dispensing machine. The fluidity of the adhesive fills the gap, and a tunnel oven is used for curing. The temperature of the first oven section is set to 130°C, and the adhesive is surface-dried after 3 minutes. The temperature of the second oven section is set to 130°C, and after 3 minutes, the adhesive is transferred to the third oven section (150°C) for curing. Curing is completed after 3 minutes, which fixes the adhesive onto the flexible PI substrate 1, thereby improving the chip packaging efficiency and packaging yield.
[0045] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0046] The raw materials used in the examples and comparative examples are as follows:
[0047] Bisphenol F type epoxy resin: Nanjing Yuelai New Material Technology Co., Ltd.: KF-8110;
[0048] Alicyclic epoxy resin: PG-207S;
[0049] Liquid bismaleimide: Shanghai Tuojing New Materials Co., Ltd.: BMI-1;
[0050] Anhydride curing agents: Zhenshi Composite Materials Co., Ltd.: Methylhexahydrophthalic anhydride type curing agent;
[0051] Accelerator: Guangdong Wengjiang Chemical Reagent Co., Ltd.: N-methylimidazole.
[0052] The components of the raw materials in Comparative Examples 1-7 and Examples 1-4 of this application, expressed as mass percentages, are shown in Table 1-2 below:
[0053] Table 1 shows the distribution ratio of each raw material group in the comparative example.
[0054]
[0055] Table 2 shows the distribution ratio of each component of raw materials in the embodiments.
[0056]
[0057] The performance of the underfill adhesives provided in Examples 1-4 and Comparative Examples 1-7 was tested, and the specific test procedures are as follows:
[0058] 1. Viscosity test method: Adjust the viscometer to level and wait for the temperature to stabilize (30℃±0.5) before installing a clean and uncontaminated rotor; take the bottom filler into a micro-cup and install it into the instrument, then adjust the speed of the viscometer to 20 rpm and read the viscosity data after it runs for 5 minutes.
[0059] 2. Flowability test: After attaching 3-9μm adhesive film to the four corners of the analog chip, fix the analog chip on the flexible substrate; after applying an appropriate amount of adhesive (adjust the amount of adhesive according to the size of the chip) around the chip using a dispensing machine, use a metallographic microscope to observe from the back of the substrate whether there are air bubbles in the circuit.
[0060] 3. Surface drying test method: Use tweezers to peel off the chip package structure after passing through three oven sections (separating the chip from the PI substrate) and observe the state of the bottom filler during the peeling process. If the bottom filler is stringy or liquid, it indicates that the adhesive has not been surface dried and is not fully cured, which does not meet the requirements for application. If the bottom filler can be separated from the PI substrate normally, it indicates that the surface drying state of the adhesive is acceptable and the degree of curing is acceptable.
[0061] 4. Surface Dryness (Cure Rate) Test: Take 5-6 mg of the adhesive and perform DSC (Differential Scanning Calorimetry) test, reading the enthalpy value H1. Take another 5-6 mg of the surface-dried adhesive sample and perform DSC test again, reading the enthalpy value H2. The cure rate under this condition is calculated using the formula (H1-H2) / H1×100%. After numerous experiments, the cure rate of this adhesive reached over 85%, and the surface dryness was within an acceptable range.
[0062] 5. Test method for peel force after surface drying: Cut the surface-dried sample into 30mm×10mm blocks, place them on the fixture of the universal tensile testing machine, fix the bottom end, clamp the top end with a tensile clamp, start the tensile mode, peel the bottom filler glue vertically from the flexible PI substrate, and read the maximum tensile force value on the tensile curve, which is the peel force.
[0063] 6. Surface tension test method: Take the adhesive liquid and place it in a sample cup, then place it in a surface tension tester to measure the value.
[0064] The test results are shown in Table 3 below:
[0065] Table 3 Test Results
[0066]
[0067] As can be seen from the table above:
[0068] (1) In Comparative Example 1, D900 polyetheramine was used as a curing agent. Although liquid bismaleimide was added to the system, it could not achieve rapid surface drying at 130°C for 3 minutes. Moreover, the curing rate of the prepared bottom filler was low and could not meet the chip packaging requirements.
[0069] (2) Compared with Comparative Example 1, no liquid bismaleimide was added in Comparative Example 2. The surface tension of the prepared bottom filler was not matched with the surface energy of the PI substrate. The wettability of the adhesive was poor and it could not completely cover the PI substrate. Using a metallographic microscope, air bubbles could be seen in the circuit from the back of the substrate.
[0070] (3) In Comparative Examples 3-4, D2000 polyetheramine with a faster reaction rate was used as a curing agent. The curing rate of the prepared bottom filler was still low and could not meet the chip packaging requirements.
[0071] (4) In Comparative Example 5, methylhexahydrophthalic anhydride was used as a curing agent, but liquid bismaleimide was not added to the system. The prepared bottom filler adhesive could not fill the gap between the PI substrate and the chip, and the adhesion to the PI substrate after curing was also low.
[0072] (5) In Comparative Example 6, the amount of methylhexahydrophthalic anhydride added was relatively small, resulting in a low curing rate of the prepared underfill adhesive. In Comparative Example 7, the amount of alicyclic epoxy resin added was relatively small, while the amount of bisphenol F epoxy resin added was relatively large, resulting in an excessively high initial viscosity of the prepared underfill adhesive. Consequently, the adhesive could not completely fill the gap between the chip and the PI substrate during the dispensing process.
[0073] (6) The bottom filler prepared by the specific formulation ratio of this application in Examples 1-4 can fill the gap between the chip and the PI substrate after dispensing, and can quickly surface dry under preset conditions with a curing rate of over 85%. It has high adhesion to the PI substrate, which can meet the chip packaging requirements and improve the reliability of chip packaging.
[0074] Finally, it should be noted that the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0075] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the invention.
[0076] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A high-adhesion underfill adhesive, characterized in that, The underfill adhesive is composed of the following components by weight percentage: 28%–54% epoxy resin, 38%–67% acid anhydride curing agent, 2%–5% accelerator, and 1%–4% additives; wherein the epoxy resin is a compound of bisphenol F type epoxy resin and alicyclic epoxy resin, and the additives include liquid bismaleimide; the viscosity of the liquid bismaleimide at 25°C is 1000–2000 cp.
2. The high-adhesion underfill adhesive according to claim 1, characterized in that, The bisphenol F type epoxy resin has a mass percentage of 14% to 27%, and the alicyclic epoxy resin has a mass percentage of 14% to 27%.
3. The high-adhesion underfill adhesive according to claim 2, characterized in that, The bisphenol F type epoxy resin has a mass percentage of 27%, and the alicyclic epoxy resin has a mass percentage of 27%.
4. The high-adhesion underfill adhesive according to claim 1, characterized in that, The hydrolytic chlorine content of the epoxy resin is less than 70 ppm.
5. The high-adhesion underfill adhesive according to claim 1, characterized in that, The structural formula of the alicyclic epoxy resin is:
6. The high-adhesion underfill adhesive according to claim 1, characterized in that, The anhydride curing agent includes methylhexahydrophthalic anhydride.
7. The high-adhesion underfill adhesive according to claim 1, characterized in that, The accelerator includes imidazole-type accelerators.
8. A method for preparing a high-adhesion underfill adhesive, characterized in that, The preparation method includes: Weigh each component of the raw material according to the mass percentage of the high-adhesion bottom filler according to any one of claims 1-7, and place them in a mixing cup to obtain the first slurry; The first slurry is stirred by a first centrifugal mixer to obtain a uniformly mixed second slurry; the operating parameters of the first centrifugal mixer include: stirring time of 150-240s, rotation of 30r / min, and revolution of 1500r / min. The second slurry is vacuum degassed using a second centrifugal mixer to obtain a bottom-filling adhesive. The operating parameters of the second centrifugal mixer include: mixing time of 100-200s, rotation of 10r / min, and revolution of 1000r / min.
9. A chip packaging structure, characterized in that, The chip packaging structure includes: a flexible PI substrate, a chip, and a high-adhesion underfill adhesive as described in any one of claims 1-7; the underfill adhesive is filled between the flexible PI substrate and the chip.
10. The chip packaging structure according to claim 9, characterized in that, The gap height between the flexible PI substrate and the chip is 3-9 μm.